Supporting Local SMEs through the Digitalization of Ecotourism Village Business in South Tangerang - Abdul Haris Muchtar; Sujoko Winanto; Zulfikar Said Agil Sidiki; Arsa Samrotul Fuadah; Aulia Islami Ansar; Eldrian Addin Naufal; Hana Hanifah; Khayla Qalisya; Sayyidah Aisyah Al-Humairah Ahmad; Muhammad Fauzan (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
The COVID-19 pandemic has had a significant impact on the economic sector, particularly MSMEs, which have struggled to adapt to the digital era. This report discusses the implementation of a community empowerment program aimed at enhancing MSMEs' ability to utilize digital marketing through social media platforms such as Instagram and Facebook. The program involved stages of FGD, surveys, socialization, training, mentoring, and evaluation. The culminating activity, a webinar titled